Pengembangan Sistem Informasi Penjualan untuk Meningkatkan Efisiensi Bisnis Mikro di Daerah Tertinggal - Firdayanti, Ayu; S, Suratno (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Limited access to technology and low digital literacy are the main challenges in managing micro businesses in remote areas. This service aims to improve the operational efficiency of micro businesses through the development and implementation of a simple and easy-to-use desktop/web-based sales information system. The implementation method includes identifying user needs, system design, training on use, and evaluating the impact of implementation. The results of the activity showed a significant increase in the efficiency of recording transactions, managing inventory, and reporting finances. This activity is expected to be a model of digital empowerment for micro business actors in similar areas.